2021
DOI: 10.1126/sciadv.abc3781
|View full text |Cite
|
Sign up to set email alerts
|

Extensive tissue-specific expression variation and novel regulators underlying circadian behavior

Abstract: Natural genetic variation affects circadian rhythms across the evolutionary tree, but the underlying molecular mechanisms are poorly understood. We investigated population-level, molecular circadian clock variation by generating >700 tissue-specific transcriptomes of Drosophila melanogaster (w1118) and 141 Drosophila Genetic Reference Panel (DGRP) lines. This comprehensive circadian gene expression atlas contains >1700 cycling genes including previously unknown central circadian clock components and tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 97 publications
2
26
0
Order By: Relevance
“…In addition to dampening, molecular oscillations of the fat body clock gradually grew out of phase with those of the brain clock over prolonged DD exposure, suggestive of a long free-running period of the fat body clock. Our observation that the fat body clock operates with a long endogenous period is consistent with the finding that expression patterns of clock genes such as tim and per exhibit 26- to 28-h periods in the fat body, as assessed by RNA sequencing of fat body tissue conducted at different time points throughout the day, while the same genes displayed ~24-h oscillations in brain tissue (Litovchenko et al, 2021). This further supports our conclusion that the fat body clock does not impact feeding behavior, since robust ~24-h feeding rhythms persist in flies kept in constant darkness despite the fact that the fat body clocks operate with long periods under these conditions.…”
Section: Discussionsupporting
confidence: 88%
“…In addition to dampening, molecular oscillations of the fat body clock gradually grew out of phase with those of the brain clock over prolonged DD exposure, suggestive of a long free-running period of the fat body clock. Our observation that the fat body clock operates with a long endogenous period is consistent with the finding that expression patterns of clock genes such as tim and per exhibit 26- to 28-h periods in the fat body, as assessed by RNA sequencing of fat body tissue conducted at different time points throughout the day, while the same genes displayed ~24-h oscillations in brain tissue (Litovchenko et al, 2021). This further supports our conclusion that the fat body clock does not impact feeding behavior, since robust ~24-h feeding rhythms persist in flies kept in constant darkness despite the fact that the fat body clocks operate with long periods under these conditions.…”
Section: Discussionsupporting
confidence: 88%
“…Our data from photoreceptors are consistent with Clk:Cyc regulating expression of several important eye-specific TFs in Drosophila photoreceptors, suggesting a mechanism through which Clk and Cyc control expression of many genes indirectly. This is likely a widespread phenomenon across Drosophila tissues because gene regulatory network analysis of cyclic transcripts in brain, gut, Malphigian tubules, and fat bodies also identified many Clock-regulated TFs, including h, hth, Mitf, and GATAd [88].…”
Section: Plos Geneticsmentioning
confidence: 99%
“…Furthermore, the GATA motif is necessary for enhancer activity in vivo, as mutating GATA motif in a reporter driven by CLK/CYC body-specific sites reduced the reporter expression in abdomens [142]. A recent study identified additional motifs and transcription factors, which drive tissue-specific circadian gene expression [125]. However, in this study, only 20% of cycling genes were shown to contain CLK/CYC binding sites [125].…”
Section: Tissue-specific Rhythmic Gene Expressionmentioning
confidence: 55%
“…These reactions are catalyzed by a group of enzymes encoded by 'Halloween genes' including phantom, disembodied, shadow, and shade, involved in the terminal hydroxylation steps (reviewed in [122]). Ecdysteroidogenic genes do not exhibit high amplitude oscillations in transcript levels in head extracts [123,124] or in other peripheral tissues [125], suggesting that regulation of ecdysteroid biosynthesis occurs in posttranscriptional level. The source of cycling 20E in the head is not clear, however, downregulation of phantom in clock neurons (LNvs) reduces the behavioral rhythmicity and slightly lengthens the circadian period [119], therefore, pacemaker neurons might be involved in the biosynthesis of 20E.…”
Section: A Potential Systemic Entrainment Cue: Ecdysonementioning
confidence: 97%
See 1 more Smart Citation